2016
DOI: 10.15585/mmwr.mm6509e2
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Reported Prevalence of Microcephaly in Infants Born to Women Living in Areas with Confirmed Zika Virus Transmission During the First Trimester of Pregnancy — Brazil, 2015

Abstract: Widespread transmission of Zika virus by Aedes mosquitoes has been recognized in Brazil since late 2014, and in October 2015, an increase in the number of reported cases of microcephaly was reported to the Brazil Ministry of Health.* By January 2016, a total of 3,530 suspected microcephaly cases had been reported, many of which occurred in infants born to women who lived in or had visited areas where Zika virus transmission was occurring. Microcephaly surveillance was enhanced in late 2015 by implementing a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
267
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(287 citation statements)
references
References 10 publications
8
267
2
7
Order By: Relevance
“…The recent outbreak of ZIKV disease in Brazil clearly favors the areas of poverty. Currently, approximately 1.5 million cases of ZIKV disease have been reported in Brazil, with the overwhelming majority of cases occurring in the poorer north-eastern states of Pernambuco, Bahia and Paraiba [42,43]. On February 1, 2016, WHO declared mosquito-borne ZIKV disease a public health emergency of international concern (PHEIC), following reports from the Brazilian Ministry of Health and PAHO [42,44].…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent outbreak of ZIKV disease in Brazil clearly favors the areas of poverty. Currently, approximately 1.5 million cases of ZIKV disease have been reported in Brazil, with the overwhelming majority of cases occurring in the poorer north-eastern states of Pernambuco, Bahia and Paraiba [42,43]. On February 1, 2016, WHO declared mosquito-borne ZIKV disease a public health emergency of international concern (PHEIC), following reports from the Brazilian Ministry of Health and PAHO [42,44].…”
Section: Transmissionmentioning
confidence: 99%
“…Currently, approximately 1.5 million cases of ZIKV disease have been reported in Brazil, with the overwhelming majority of cases occurring in the poorer north-eastern states of Pernambuco, Bahia and Paraiba [42,43]. On February 1, 2016, WHO declared mosquito-borne ZIKV disease a public health emergency of international concern (PHEIC), following reports from the Brazilian Ministry of Health and PAHO [42,44]. Because there is a debate regarding the relationship between poverty and ZIKV transmission, ZIKV disease may not be a condition that affects only poor people because vector mosquitoes can breed in stagnant water, even in developed regions of the world, and can bite anyone.…”
Section: Transmissionmentioning
confidence: 99%
“…Finally, congenital malformations associated with ZIKV infection described in recent studies 4,5,6,7,30,34 and a protocol of the Brazilian Ministry of Health 28 were classified according to ICD-10. These include a broad range of congenital malformations of the brain and eye.…”
Section: A Review Of Icd Codes In the Con-text Of Zikv Outbreaks And mentioning
confidence: 99%
“…Recent studies have shown that ZIKV infection damages the central nervous system, causing fetal malformations 1 and certain neuropathies such as GuillainBarré Syndrome [2][3][4][5] . The virus's neurotropic behavior and its ability to cross the placental barrier and cause brain damage during fetal development have been demonstrated in laboratory experiments 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…By September, increasing numbers of cases of microcephaly were being reported, particularly from regions involved in the Zika virus outbreak. 10 Evidence of a link between Zika virus infection in pregnancy, particularly during the first trimester, and microcephaly in the fetus mounted [11][12][13] and a causal association between Zika virus infection and microcephaly and/or other birth defects was formally established. 14 The majority of women in whom microcephaly of the fetus was diagnosed reported some symptoms of Zika virus infection at some point during their pregnancy, usually in the first or second trimester; rash was the most common symptom reported.…”
mentioning
confidence: 99%